2022
DOI: 10.21926/obm.neurobiol.2203130
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Resistance Resources in the Time of COVID-19: The Role of Sense of Coherence and Resilience in the Relationship between COVID-19 Fear and Loneliness among Schoolteachers

Abstract: Fear has been the most common emotional response to the COVID-19 pandemic, and excessive fear is associated with various indices of psychological distress, particularly loneliness. Although most people have experienced pandemic-related fear and distress, certain groups who are on the front of service provision have experienced the pandemic in distinct ways, owing to its impact on the nature of their work. Schoolteachers represent one such group; therefore, it is imperative to identify resources that can safegu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…The author of the scale provided a review of the psychometric properties of the scale and found reliability coefficients ranging between 0.74 and 0.91, and evidence for construct and criterion validity across 16 studies [18]. In South Africa, the SOC-13 was used with both a student [29] and teacher sample [30], yielding reliability coefficients of 0.814 in both samples. The reliability of the SOC-13 was satisfactory in the current study (α = 0.83).…”
Section: Methodsmentioning
confidence: 99%
“…The author of the scale provided a review of the psychometric properties of the scale and found reliability coefficients ranging between 0.74 and 0.91, and evidence for construct and criterion validity across 16 studies [18]. In South Africa, the SOC-13 was used with both a student [29] and teacher sample [30], yielding reliability coefficients of 0.814 in both samples. The reliability of the SOC-13 was satisfactory in the current study (α = 0.83).…”
Section: Methodsmentioning
confidence: 99%